A revision of the continental species of Copa Simon, 1885 (Araneae, Corinnidae) in the Afrotropical Region - Haddad, Charles Richard (Pensoft Publishers, 2013)

(untitled)
Abstract. The cryptic ground-dwelling castianeirine genus Copa Simon, 1885 (Araneae: Corinnidae) is revised in the continental Afrotropical Region. The type species of the genus, Copa flavoplumosa Simon, 1885, is redescribed and considered a senior synonym of Copa benina Strand, 1916 syn. n. and Copa benina nigra Lessert, 1933 syn. n. It is widespread throughout the Afrotropical Region but has not been introduced to any of the associated regional islands. A new species, Copa kei sp. n., is described from South Africa. Copa agelenina Simon, 1910, originally described from a subadult female from southern Botswana, is considered a nomen dubium. Copa flavoplumosa is a characteristic species of leaf litter spider assemblages and is particularly prevalent in savanna habitats on the continent, but also occurs in various forest types, grasslands, fynbos and semi-arid Nama Karoo habitats. In contrast, Copa kei sp. n. has only been recorded from Afromontane and coastal forests in south-eastern South Africa.